2020
DOI: 10.21037/atm-20-1620
|View full text |Cite
|
Sign up to set email alerts
|

Upfront debulking surgery for high-grade serous ovarian carcinoma: current evidence

Abstract: High-grade serous ovarian carcinoma (HGSOC) is a leading cause of mortality among women worldwide. Currently, there is no clear consensus over the regime these patients should receive. The main two options are upfront debulking surgery with adjuvant chemotherapy or neoadjuvant chemotherapy followed by interval debulking surgery (IDS). The former approach is proposed to be accompanied by lower chemoresistance rates but could lead to severe surgical comorbidities and lower quality of life (QoL). Optimizing patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…In many clinical practices, complete tumor resection is difficult and debulking surgery is usually used to relief the patient’s symptoms for some advanced tumors such as ovarian carcinoma, neoplasms of central nervous system and lymphoma [ 17 ]. In order to prolong the patients’ lifetimes, efforts have been devoted to explore new intraoperative adjuvant techniques to impede the residual tumour growth, such as intraoperative radiotherapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many clinical practices, complete tumor resection is difficult and debulking surgery is usually used to relief the patient’s symptoms for some advanced tumors such as ovarian carcinoma, neoplasms of central nervous system and lymphoma [ 17 ]. In order to prolong the patients’ lifetimes, efforts have been devoted to explore new intraoperative adjuvant techniques to impede the residual tumour growth, such as intraoperative radiotherapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…HGSOC has the tropism of omental fat and can be used as an energy source. The inability to detect the disease in early diagnosis is one of the main factors for the higher mortality of HGSOC patients [ 3 ]. Studies have shown that only about 13% of serous ovarian cancer cases are diagnosed in stage I or II [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16] In many clinical practices, complete tumor resection is difficult and debulking surgery is usually used to relief the patient's symptoms for some advanced tumors such as ovarian carcinoma, neoplasms of central nervous system and lymphoma. [17] In order to prolong the patients' lifetimes, efforts have been devoted to explore new intraoperative adjuvant techniques to impede the residual tumour growth, such as intraoperative radiotherapy. [18] However, intraoperative radiotherapy can induce ionizing radiation damage.…”
Section: Introductionmentioning
confidence: 99%